2016
DOI: 10.1016/j.jphotochem.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and photochemical properties of manganese complexes with cationic porphyrin ligands: Effects of alkyl substituents and micellar environment

Abstract: Although Mn(III) porphyrins were considered earlier to be very weakly emissive, the fluorescence displayed by Mn(III) complexes with the cationic TMPyP 2+ ligand (H2TMPyP 4+ = 5,10,15,20-tetrakis(1-methylpyridinium-4-yl)porphyrin) as well as with its other alkyl (such as hexyl and dodecyl) derivatives proved to be strong enough for a comparative study. Elongation of the alkyl substituent increased both the quantum yield and the lifetime of the emission for the Mn(III) porphyrins, while resulted in an opposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Accordingly, porphyrin complexes of low-spin Mn(III) and Co(III) were considered to be very weakly fluorescent. However, current investigations using a more sensitive equipment indicated that both Mn(III)TMPyP 5+ and Co(III)TMPyP 5+ display a characteristic fluorescence in the 600-750-nm range (Fig 2), which is more than an order of magnitude weaker (fl = 1.110 -4 and 1.410 -3 for the Mn(III) and Co(III) complexes, respectively [16,17]) than that exhibited by the corresponding free base (0.047 [18], 0.030 [19]). The shorter emission lifetimes of these complexes are also in accordance with this tendency caused by both electronic and steric interactions between the metal center and the ligand in these hyper-porphyrins.…”
Section: Photophysics and Photoredox Chemistry Of Water-soluble In-plmentioning
confidence: 90%
See 1 more Smart Citation
“…Accordingly, porphyrin complexes of low-spin Mn(III) and Co(III) were considered to be very weakly fluorescent. However, current investigations using a more sensitive equipment indicated that both Mn(III)TMPyP 5+ and Co(III)TMPyP 5+ display a characteristic fluorescence in the 600-750-nm range (Fig 2), which is more than an order of magnitude weaker (fl = 1.110 -4 and 1.410 -3 for the Mn(III) and Co(III) complexes, respectively [16,17]) than that exhibited by the corresponding free base (0.047 [18], 0.030 [19]). The shorter emission lifetimes of these complexes are also in accordance with this tendency caused by both electronic and steric interactions between the metal center and the ligand in these hyper-porphyrins.…”
Section: Photophysics and Photoredox Chemistry Of Water-soluble In-plmentioning
confidence: 90%
“…The shorter emission lifetimes of these complexes are also in accordance with this tendency caused by both electronic and steric interactions between the metal center and the ligand in these hyper-porphyrins. [16,17].…”
Section: Photophysics and Photoredox Chemistry Of Water-soluble In-plmentioning
confidence: 99%
“…Due to this band slightly redshifted compared to that of the free base, Ni(II) porphyrins were categorized as hypso type [4,27]. The emission spectrum displayed by Ni(II)TMPyP 4+ upon Soret-band excitation (Fig 2) is very similar to those of the corresponding cationic Co(III) and Mn(III) metalloporphyrins [7,17]. The fluorescence bands in the 550-800-nm range of the fluorescence spectra of porphyrins, both metalloporphyrins and free bases, can be assigned as S1S0 transitions (the individual bands correspond to the (0, 0), (0,1) and (0,2) transitions with respect to vibrational states -the latter one is generally not perceptible ) [19].…”
mentioning
confidence: 93%
“…However, while the photoredox chemistry of iron(III) and cobalt(III) porphyrins was thoroughly studied in the past 2-3 decades [6,7,8,9,10], the corresponding nickel(II) complexes were hardly examined in this respect [11,12]. Since the complexes of iron(III), cobalt(III) as well as manganese(III) with the cationic 5,10,15,20-tetrakis(1-methylpyridinium-4-yl)porphyrin (H2TMPyP 4+ ) proved to be promising in various photocatalytic systems [3,7,8,13,14,15,16,17], in this work some photophysical and photochemical properties of Ni(II)TMPyP 4+ were studied in order to examin the potential applicability of this metalloporphyrin in utilization of solar radiation in the visible range.…”
mentioning
confidence: 99%
See 1 more Smart Citation